Empowering Women's Business Groups through Microfinance in Village Enterprises - Khafidz, Abdul; Agustina, Isna Fitria (Indonesian Journal of Cultural and Community Development, 2025)
Background: Effective management of microfinance institutions is essential for rural economic development. Specific Background: This study examines BUMDesa Bersama “Gempol Sejahtera,” focusing on its application of microfinance principles in financial management. Knowledge Gap: There is limited research on how structured bureaucracies affect the success of microfinance programs in community organizations. Aims: The research evaluates the impact of organizational structure on microfinance initiatives and resource management. Results: Findings show that a clear bureaucratic structure enhances efficiency and role clarity, facilitating successful program implementation. Clear Standard Operating Procedures (SOPs) and task fragmentation are critical for optimal execution. Novelty: This study offers new insights into the link between organizational structure and microfinance effectiveness in community enterprises, enriching the literature on rural empowerment. Implications: The results underscore the importance of strong organizational frameworks to improve resource management and program responsiveness, thereby promoting economic empowerment, especially among women. Highlights : Organizational Efficiency: A clear bureaucratic structure enhances operational effectiveness and role clarity. Critical Procedures: Implementing Standard Operating Procedures (SOPs) is essential for program success. Economic Empowerment: Strong frameworks promote responsiveness and resource management, benefiting community initiatives. Keywords: microfinance, organizational structure, community empowerment, financial management, bureaucratic efficiency